Sustaining crop production in China's cropland by crop residue retention: A meta‐analysis - Zhao, Xin; Liu, Bing‐Yang; Liu, Sheng‐Li; Qi, Jian‐Ying; Wang, Xing; Pu, Chao; Li, Shuai‐Shuai; Zhang, Xiong‐Zhi; Yang, Xiao‐Guang; Lal, Rattan; Chen, Fu; Zhang, Hai‐Lin (Land degradation & development, 2020)
Crop residue retention (RR) is a recommended practice in China and globally. However, comprehensive assessment of changes and mechanisms affecting crop production and soil processes with RR and thus identifying systems of sustainable residues management are not widely studied. A national meta‐analysis was conducted to assess changes in 24 indicators (related to soil quality, soil nutrients, crop yield, and environmental impacts) along with their relationships under RR through 4,910 comparisons from 278 publications across China's croplands. Positively, RR significantly increased crop yield (7.8%), soil organic carbon (SOC) pool (12.3% to 36.8%), soil nutrient reserves (1.9% to 15.2%), soil temperature (6.7%), and water contents (5.9%) and improved soil structure when compared with residue removal (P < .05). Negatively, RR may increase soil acidification and significantly increase emissions of greenhouse gases (by 31.7%, 130.9%, and 12.2% for CO2, CH4, and N2O). Nonetheless, the negative effects can be alleviated, and the positive effects can be strengthened by adopting RR in conjunction with appropriate crops, specific farming practices, and avoiding more than 10 years of consecutive use. The results indicated that a higher decomposition of native and newly added organic matters, induced by RR and attendant changes in soil physical properties, could enhance the dynamics of SOC, microbial biomass, soil nutrients, and the final increase in crop yield and greenhouse gases emissions. Thus, the sustainability of RR‐based system could be enhanced by a careful choice and adoption of integrated farming practices. Proper RR management strategies could offer a climate‐smart solution to ensure food security and sustain soil productivity.